Haematopoietic Stem Cell Transplant Trends in Pakistan: Activity Survey from Pakistan Bone Marrow Transplant Group - Natasha Ali; Raheel Iftikhar; Muhammad Ayaz Mir; Syed Waqas Bokhari; Jehanzeb Ur Rehman; Uzma Zaidi; Shahzad Nasir; Salman Naseem Adil; Tariq Satti; Qamar Un Nisa Chaudhry; Muhammad Farhan; Tasneem Farzana; et al. (Journal of Transplantation)
Pakistan is the fifth most populous country with a population of 225 million and has health expenditure accounting for only 2.8 percent of gross domestic product (GDP). Accordingly, there are a limited number of haematology-oncology and transplant centers in the country. The Pakistan Blood and Marrow Transplant (PBMT) group was established in 2020, and this report is the first activity survey from January 2021 to December 2022 focusing on the trends of matched-related donor, haploidentical, and autologous transplants in a developing country. A total of 12 transplant centers contributed data on the modified PBMT survey form retrospectively and 806 haematopoietic stem cell transplants (HSCTs) were carried out during the study duration. Allogeneic HSCT constituted 595 (73.8%) of all the transplants; this is in stark contrast to Western data, where autologous HSCT accounts for the majority of transplants. ß-thalassemia major and aplastic anemia were the commonest indications for allogeneic HSCT, in contrast to Western data, where acute leukemia is the leading transplant indication. Autologous transplants were more frequently performed for Hodgkin’s lymphoma as compared to non-Hodgkin’s lymphoma and multiple myeloma. The use of peripheral and bone marrow stem cells was comparable. A myeloablative conditioning regimen was routinely used in patients with acute leukemia. This report provides an insight of HSCT trends in Pakistan which are different from those of Western centers contributing to transplant data from South Asia.